The establishment mode decision between Acquisition and Greenfield investment into the Russian market: Case study, a retail company - Lelo de Larrea Gaudiano, Christian (My University, 2013)
The aim of this study was to suggest a Finish retail company the establishment mode choice to internationalize into the Russian market, between Acquisition and Greenfield Investment mode of entries. Based on literature theory, a theoretical framework was developed to answer the research question and formulate propositions for the study. The research consisted of a qualitative case study. The study was analyzed by testing the theoretical framework on three Finnish International companies and then later on applied to the case company. Structured thematic interviews were conducted as the primary source for data collection. The interviews and analysis were based on the theoretical framework. The main findings provide several recommendations for the case company and the retail industry when internationalizing for the first time to the Russian market. As the case company lacks, experience in an international manner, knowledge on the Russian culture, assets in the Russian market such as networks with suppliers, government administration, real estate, logistics, brand name, reputation, purchasing department fitted to understand the Russian culture, the case company is suggested to internationalize to the Russian market via acquisition mode of entry. Using this method it will enable it to tap into the core resources needed to operate in the retail industry in Russia. The thesis provides comprehensive guidance to the decision of choosing acquisitions or greenfield investments when internationalizing into the Russian market.
Keywords: Acquisition; Greenfield Investment; Russian Retail Market; Foreign Direct Investment; Establishment Mode Choice; Retail Internationalization; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|